An Alternative Autophagy-Related Mechanism of Chloroquine Drug Resistance in the Malaria Parasite - Kamil, Mohd; Atmaca, Habibe N.; Unal, Sinem; Kina, Umit Y.; Burak, Pinar; Deveci, Gozde; Yilmaz, Ilknur; Aly, Ahmed S., I (AMER SOC MICROBIOLOGY, 2022)
We generated highly chloroquine (CQ)-resistant (ResCQ) Plasmodium yoelii parasites by stepwise exposure to increasing concentrations of CQ and CQ-sensitive parasites (SenCQ) by parallel mock treatments. No mutations in genes that are associated with drug resistance were detected in ResCQ clones. Autophagy-related genes were highly upregulated in SenCQ compared to ResCQ parasites during CQ treatment. This indicates that CQ resistance can be developed in the malaria parasite by the inhibition of autophagy as an alternative drug resistance mechanism.
Keywords: malaria; Plasmodium yoelii; chloroquine; drug resistance; autophagy; drug resistance mechanisms; TRANSMEMBRANE PROTEIN PFCRT; PLASMODIUM-FALCIPARUM; MUTATIONS; QUININE; DEATH; Microbiology; Pharmacology & Pharmacy